2010
DOI: 10.1152/ajplung.00123.2010
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide hyperpolarizes guinea pig airway epithelium by increasing the activities of the epithelial Na+ channel and the Na+-K+ pump

Abstract: Earlier, we found that systemic administration of lipopolysaccharide (LPS; 4 mg/kg) hyperpolarized the transepithelial potential difference (V(t)) of tracheal epithelium in the isolated, perfused trachea (IPT) of the guinea pig 18 h after injection. As well, LPS increased the hyperpolarization component of the response to basolateral methacholine, and potentiated the epithelium-derived relaxing factor-mediated relaxation responses to hyperosmolar solutions applied to the apical membrane. We hypothesized that L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 64 publications
0
8
2
Order By: Relevance
“…Moreover, it has also been reported that ENaC expression was not affected by LPS induction (9,12). In human H441 airway epithelial cells, α-ENaC mRNA and protein levels have been observed to be downregulated by LPS (10).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Moreover, it has also been reported that ENaC expression was not affected by LPS induction (9,12). In human H441 airway epithelial cells, α-ENaC mRNA and protein levels have been observed to be downregulated by LPS (10).…”
Section: Discussionmentioning
confidence: 92%
“…LPS is a prototypical endotoxin that is a key component of the outer membrane of gram-negative bacteria, including Pseudomonas aeruginosa. LPS has been demonstrated to modify Na + transport in the airway epithelium by regulating either ENaC mRNA expression (8) or the ENaC channel current (9). The effect of LPS on α-ENaC expression in rats and airway cell lines is controversial, as expression has been observed to increase and decrease (10,11), and in certain studies, to remain unchanged following LPS induction (9,12).…”
Section: Introductionmentioning
confidence: 99%
“…In present study, baicalin prevented the inhibitory effect of LPS on the number of cells expressing α-ENaC in rats with ALI, and reversed the decrease of α-ENaC protein expression induced by LPS in vitro. Numberous previous studies have reported that α-ENaC may be regulated by LPS, however, these findings are controversial, as both increased and decreased effect in α-ENaC expression were observed (Baines et al 2010;Dodrill and Fedan 2010). Until recently, Daginais et al 2005 andSheng et al 2014 has demonstrated that LPS may modulate α-ENaC expression in a biphasic manner, with a transient increase in the early stage and a sustained decrease thereafter.…”
Section: Discussionmentioning
confidence: 99%
“…Beside ENaC, a nonselective nucleotide-gated cation channel contributes to apical Na + absorption in rat airway epithelium (trachea, bronchi, and bronchioles) [33]. On the basolateral side, Na + is secreted from the cells by the Na + /K + ATPase that is ubiquitously expressed in airway epithelia and provides the driving force for apical Na + reabsorption [34, 35]. Thus, the Na + /K + ATPase together with the ENaC mediate transcellular Na + reabsorption.…”
Section: The Airway Epitheliummentioning
confidence: 99%
“…Cultures of one single epithelial cell type, such as rabbit bronchiolar Clara cells, have also been used [21]. Besides cultured cells, freshly isolated intact tissues are used to study airway epithelial ion transport such as murine trachea [23], equine trachea [45], pig trachea [13], guinea pig trachea [35], and sheep trachea [66]. Thus, considering the variety of available models from different species and airway epithelial types for characterising airway epithelial ion transport, it is important to carefully choose the model according to the problem that needs to be investigated.…”
Section: The Airway Epitheliummentioning
confidence: 99%